(untitled) (Research, Society and Development, 2021)
The purpose of the article is to present the results of the research on patient safety from the perceptions of the employees of high complex hospital, located in the southern region of Brazil. It is applied, transversal, exploratory and descriptive research, with survey design and quantitative approach. Data collection was performed using the Hospital Survey on Patient Safety Culture (HSOPSC), developed by the Agency for Healthcare Research And Quality and validated in Brazil by Reis (2013). 646 (67%) of the 960 hospital employees participated in the survey. The main results of the study were identified as strong dimensions for patient safety ’organizational learning’, ’hospital management support for patient safety’, ’frequency of reported events’ and’ expectations about your supervisor / boss’ and ’actions promoting patient safety. Otherwise, the dimensions ‘shift change / shift’ and ‘non-punitive responses to errors’ were characterized as fragile for the safety culture in the hospital. Therefore, reinforcing the promoter aspects and intervening in the weakening aspects represent urgent and necessary actions to be taken in the hospital in question, as well as in the entire hospital system.